Defense and Security Mechanisms in the Internet of Things: A Review - Sabina Szymoniak; Jacek Piątkowski; Mirosław Kurkowski (Applied Sciences)
The Internet of Things (IoT) transforms traditional technology by introducing smart devices into almost every field, enabling real-time monitoring and automation. Despite the obvious benefits, the rapid deployment of IoT presents numerous security challenges, including vulnerabilities in network attacks and communication protocol weaknesses. While several surveys have addressed these aspects, there remains a lack of understanding of integrating all potential defense mechanisms, such as intrusion detection systems (IDSs), anomaly detection frameworks, and authentication protocols, into a comprehensive security framework. To overcome this, the following survey aims to critically review existing security mechanisms in IoT environments and significantly fill these gaps. In particular, this paper reviews state-of-the-art approaches for intrusion detection, key agreement protocols, and anomaly detection systems, pointing out their advantages and disadvantages and identifying the gaps in each field requiring more research. We identify innovative strategies by systematically analysing existing approaches and propose a roadmap for enhancing IoT security. This work contributes to the field by offering a fresh perspective on defense mechanisms and delivering actionable insights for researchers and practitioners securing IoT ecosystems.